Role of anti-Mullerian Hormone and Gamma-‎glutamyl-transpepetidase in the Sera and ‎Seminal Plasma in Infertile Men in Baghdad (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The study was carried out through the period from February /2015 to June 2015, for estimation the concentration of anti-Mullerian hormone ( AMH) in the seminal plasma & sera of infertile males compared with healthy group as control , also the gamma-glutamyltranspeptidase level were measured in the seminal plasma and sera of patients and healthy , (79 ) infertile male and ( 32 ) healthy , with age ranged from( 18 – 49 ) year for both groups .The diagnosis done by macroscopic and microscopic examination of semen according to W.H.O. standard criteria. A significant decrement (P (0.05 > was observed for male with oligozoospermia as compared to other groups of male infertility factor.  There was significance elevation (P (0.05>for male complaining from teratozoospermic as compared to normozoospermic , oligozoospermic  and a zoospermia.Similarly, significant Increment (P (0.05 >in seminal plasma (AMH) for male suffering from oligozoospermia compared to other groups. Meanwhile teratozoospermic patients showed significant increment P 0.05 >as compared with other infertile groups. Also azoospermic patients revealed significant reduction P 0.05 >in the concentration of seminal plasma AMH compared with other infertile group.Normozoospermic male showed a significant (P > 0.05) elevation in the concentration of GGT when compared with other infertile groups . Teratozoospermic patientsshowed a significant decrement (P( 0.05 >  in the concentration of GGT . A stheuozoopermic patients showed significant elevation (p ≤ 0.05) of concentration of seminal fluid GGT, while oligozoospermia  patients significant decrement (P (0.05 >as compared with other infertile groups